CURRENT STATE OF RESEARCH IN THE FIELD OF CHEMICAL COMPOSITION AND PHARMACOLOGICAL EFFECTS OF ZEA MAYDIS STYLI CUM STIGMATIS - E. B. Nikiforova; N. M. Bat; N. A. Davitavyan (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
Zea maydis styli cum stigmatis (Engl. corn silk) are well known in medical practice. In the scientific literature, a lot of information has been accumulated about the chemical composition and pharmacotherapeutic actions of this medicinal plant material. A chronological analysis of this information shows that earlier, the scope of scientific publications was mainly devoted to the study of the choleretic, diuretic, hemostatic kinds of Zea maydis styli cum stigmatis activity, and the identification of the active substances responsible for these types of action. Currently, there is a growing scientific interest not only in the individual natural compounds of the Zea maydis styli cum stigmatis composition, but also in the search for new aspects of their medical application.The aim of the article is a review and systematization of modern scientific data in the field of the Zea maydis styli cum stigmatis chemical composition and their pharmacological action.Materials and methods. For the information and analytical search, the scientific data posted on the following electronic resources were used: PubMed, Web of Science, ScienceDirect, Scopus, Google Scholar, eLibrary. The search was carried out in the period from 2005 to 2021 using the following keywords: Zea mays L.; Zea maydis styli cum stigmatis; corn silk; chemical composition; pharmacological action.Results. The review is devoted to the generalization and analysis of modern scientific data on the Zea maydis styli cum stigmatis chemical composition and their pharmacological action. It has been shown that, as before, the greatest attention of scientists is attracted by flavonoids in the Zea maydis styli cum stigmatis chemical composition. Alongside with them, phenolcarboxylic acids, vitamin K, phytosterols, volatile compounds and polysaccharides are of no small importance for the Zea maydis styli cum stigmatis pharmacological activity. Modern ideas about the Zea maydis styli cum stigmatis pharmacological activity have been expanded by summarizing the study results of their antioxidant, anti-inflammatory, antidiabetic, hypotensive, neuro- and photoprotective activities. The data on the effectiveness of their use as parts of the complex tumor diseases therapy have been published.Conclusion. As a result of the data analysis of modern scientific literature, it has been found out that Zea maydis styli cum stigmatis are still in the sphere of scientists' interest. Alongside with the flavonoids of this raw material, other groups of pharmacologically active substances are also being actively studied. It has been revealed that the information about potentially significant and confirmed types of the Zea maydis styli cum stigmatis therapeutic action is significantly updated. The results of this review may be useful for identifying promising directions for the development of the drugs based on Zea maydis styli cum stigmatis.